2021
DOI: 10.1111/jipb.13066
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive identification of lysine 2‐hydroxyisobutyrylated proteins in Ustilaginoidea virens reveals the involvement of lysine 2‐hydroxyisobutyrylation in fungal virulence

Abstract: Lysine 2-hydroxyisobutyrylation (K hib) is a newly identified post-translational modification (PTM) that plays important roles in transcription and cell proliferation in eukaryotes. However, its function remains unknown in phytopathogenic fungi. Here, we performed a comprehensive assessment of K hib in the rice false smut fungus Ustilaginoidea virens, using Tandem Mass Tag (TMT)-based quantitative proteomics approach. A total of 3 426 K hib sites were identified in 977 proteins, sugg esting that K hib is a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…Khib has recently been reported in F. oxysporum , B. cinerea , and U. virens . In U. virens , disruption of 2-hydroxyisobutyrylation in the MAPK pathway kinase UvSlt2 by mutation decreases fungal virulence ( Chen et al, 2021 ). In the comprehensive analysis of F. oxysporum , critical proteins for virulence – FoFmk1, FoHog1 and two MAP kinase signaling proteins – have been identified ( Qian et al, 2021 ); For B. cinerea , many 2-hydroxyisobutyrylated proteins are involved in substance synthesis and metabolism, redox and autophagy, kinase and protease, and are associated with the pathogenicity of B. cinerea ( Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khib has recently been reported in F. oxysporum , B. cinerea , and U. virens . In U. virens , disruption of 2-hydroxyisobutyrylation in the MAPK pathway kinase UvSlt2 by mutation decreases fungal virulence ( Chen et al, 2021 ). In the comprehensive analysis of F. oxysporum , critical proteins for virulence – FoFmk1, FoHog1 and two MAP kinase signaling proteins – have been identified ( Qian et al, 2021 ); For B. cinerea , many 2-hydroxyisobutyrylated proteins are involved in substance synthesis and metabolism, redox and autophagy, kinase and protease, and are associated with the pathogenicity of B. cinerea ( Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of Khib have been reported in plants, such as developing rice seeds ( Meng et al, 2017 ), common wheat ( Bo et al, 2021 ; Zhang et al, 2021 ) and Physcomitrella patens ( Yu et al, 2017 ); Histone H4K8 2-hydroxyisobutyrylation (H4K8 hib) has been identified as an evolutionarily conserved modification in Saccharomyces cerevisiae ( Huang et al, 2017 ). Some reports have described Khib in biological pathogens, such as the animal pathogens Proteus mirabilis , Toxoplasma gondii , and Candida albicans ( Dong et al, 2018 ; Yin et al, 2019 ; Zheng et al, 2021 ), Khib in plant pathogens has also been reported, such as Fusarium oxysporum , Botrytis cinerea , and Ustilaginoidea virens ( Xu et al, 2020 ; Chen et al, 2021 ; Qian et al, 2021 ). Reports on these three pathogens have revealed that Khib is widely distributed in cellular compartments and is involved in diverse cellular processes, including regulation of pathogenicity and virulence.…”
Section: Introductionmentioning
confidence: 99%
“…In Escherichia coli, CobB serves as a K hib deacylase (Dong et al, 2019). UvRpd3 was recently reported to function as the main enzyme that removes K hib in Ustilaginoidea virens (Chen et al, 2021). However, the key regulatory enzymes involved in K hib homeostasis in rice have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was evidence that K hib modification may introduce the conformational changes of Enolase1 and alter the substrate binding [ 148 ]. K hib increased the hydrophobic solvent-accessible surface area and decreased the enzymatic activity of UvSlt2 [ 149 ].…”
Section: Starch Biosynthesis-related Proteins Targeted By Ptmsmentioning
confidence: 99%